PENGARUH PROFITABILITAS, PAJAK DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN MELALUI STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Fajar Eka Prasetyo; Fifi Swandari; Dian Masita Dewi (Universitas Lambung Mangkurat, 2017)
This study aims to analyze the direct effects on profitability, taxes and growth opportunity on firm value as well as the indirect influence for profitability, tax and growth opportunity to firm value through a capital structure oncompanies and mining companies listed in Indonesia Stock Exchange in 2011-2014 period. The results showed that (i) profitability and growth opportunity hada positive effect on the capital structure, (ii) taxes hada negative effect on the capital structure, (iii) profitability and capital structure hada positive effect on firm value, (iv) taxes and growth opportunity hadno effect on firm value, (v) profitability and growth opportunity affected firm value through a capital structure as an intervening variable.Multinational companies and mining companies in Indonesia Stock Exchange tried to use external funding to run their operations to shrink the tax paid in order to obtain large profits and to increase firm value.